A Study of the Mechanical Properties of Au Nanomeshes. (25th May 2020) - Li, Dongjing; Li, Ganming; Wan, Qing; Xu, Wuxiong; Liu, Jianghua; Li, Zeping
Abstract : We study the mechanical behavior of Au nanomeshes (AuNMs) based on finite element analysis (FEA) simulation and deformation tests. The simulated results of mechanical flexibility indicate that polyethylene terephthalate (PET) substrate can release the stress of AuNMs under mechanical stretching and bending, the displacement of stretched AuNMs yields a 2% promotion, and the displacement of bent AuNMs yields a 3.5% promotion under buffering of PET substrate at 5 GPa yield strength of nanoscale Au. The stress and displacement distribution of the AuNMs/PET is demonstrated and analyzed. The further deformation tests of AuNMs under compressive and tensile loading indicate that the simulation data are in good agreement with experimental results. This paper is conducive to understanding the mechanical behavior and corresponding structural response and structural fracture dynamics of AuNMs.